2013
DOI: 10.1108/ijchm-jul-2012-0112
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for people with disabilities in visiting casinos

Abstract: Purpose – The purpose of this paper is to examine the barriers identified by people with disabilities in visiting casinos. Design/methodology/approach – Face-to-face interviews were conducted with 12 people with disabilities recruited from the investigator's clinical and community networks and personal referrals, and 18 casino supervisors and dealers who attended a casino diploma course offered by a university. The data were subjected to thematic content analysis. Findings – The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…The literature shows that women with disabilities are doubly disadvantaged because of gender and disability-related exclusion (De Pascale et al, 2023). Major travel barriers among TWDs were accessibility and intrapersonal and interpersonal aspects (Wan, 2013;Kong and Loi, 2017). Lee et al (2012) discovered that the intrinsic and environmental factors positively and significantly influenced TWDs' travel decisions.…”
Section: Disability Inclusion Enablersmentioning
confidence: 99%
“…The literature shows that women with disabilities are doubly disadvantaged because of gender and disability-related exclusion (De Pascale et al, 2023). Major travel barriers among TWDs were accessibility and intrapersonal and interpersonal aspects (Wan, 2013;Kong and Loi, 2017). Lee et al (2012) discovered that the intrinsic and environmental factors positively and significantly influenced TWDs' travel decisions.…”
Section: Disability Inclusion Enablersmentioning
confidence: 99%
“…The results of Yim's (2013) study on the barriers identified by PwSN while visiting casinos in Macao reveal that the structural constraints (e.g. insufficient facilities and accessibility, insufficient space, blockage of entrances, insufficient information, financial barriers) and interpersonal constraints (social exclusion, insufficient communication, poor staff service) stand out as being the main ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently the accessible tourism market (which includes PwD, people with other functional limitations and elderly) is already a highly significant market. PwD represent about 15% of the whole world's population (World Bank, 2020), and this is expected to grow greatly due to the aging of the population (Alves et al , 2020; Blichfeldt and Nicolaisen, 2011; Carneiro et al , 2022; Darcy, 2002; Darcy and Pegg, 2011; Eusébio et al , 2022; Ozturk et al , 2008; Pagán-Rodríguez, 2014; Rucci and Porto, 2022; Small and Darcy, 2010; Yim, 2013). Moreover, engagement in tourism activities has a great impact on the well-being of participants (Eusébio and Carneiro, 2014; McCabe, 2009; Moura et al , 2022; Small and Darcy, 2010) and people feel different when they travel.…”
Section: Introductionmentioning
confidence: 99%
“…Service providers’ social attitudes and responsiveness make it harder for them to achieve CwD’s standards. Institutional, informational and attitudinal barriers prevent CwD from accessing services, making their lives difficult (Khumalo and Ndlovu, 2017; Wan, 2013; Yu et al , 2015). These issues arise because CwD service design mostly takes a medical approach (Khumalo and Ndlovu, 2017; Nicolaisen et al , 2012; Ravneberg, 2009) instead of focusing on the social model (CwD sensitivities and interpersonal relationships).…”
Section: Thematic Analysismentioning
confidence: 99%
“…Most of the time, CwD’s disability breeds prejudice and stereotypes that negatively affect how these consumers are viewed and how they can access services (Rossow-Kimball and Goodwin, 2018; Stumbo et al , 2011). As a result, CwD feels included and accepted in a service context when facility-specific and attitudinal elements of service employees and other customers come together (Baker et al , 2007; Nicolaisen et al , 2012; Wan, 2013).…”
Section: Thematic Analysismentioning
confidence: 99%